Evaluating the Skills of Tajweed and Recitation of Holy Quran in the Primary Instruction Program - Specialization of Islamic Studies at Faculty of Education – University of Bisha - Elaalim, Osman Mohamed Hamid; Elsanosi, Mohammed Yousif Ahmed (Journal of Educational and Psychological Sciences, 2021)
The research aims to identify the degree to which student teachers at the primary education program in Islamic studies specialization can master the skills of Tajweed and recitation of Holy Qur’an. The researchers followed the descriptive analytical approach, using: observation card; that was applied to a sample of (22) student teachers at the College of Education, University of Bisha, and a questionnaire was applied to a sample of (35) student teachers. The method of content analysis for the courses of Tajweed and recitation in the program reached (5) courses. The most important results of the research: Student teachers were able in Tajweed and recitation, in light of the objectives of the program’s courses, in most of the observation results with an arithmetic mean indicated mastery with an average score of (2.8), a few with an average of (1.8), and very few with an average (1.2). The value of the arithmetic mean for the total observations reached (2.0), that is, the performance was to a small degree according to Likert scale with a standard deviation (0.98). While most of the student teachers’ mastery results, from their point of view, indicate that they have an average score of (2.6), a very large with an average (4.0), and that the value of the arithmetic mean is (3.5), that is the performance is highly according to Likert scale, On the availability of Tajweed and recitation skills in the program; the lack of repetitions in some skills were observed, and their increase in others. This confirms the importance of conducting this research and suggesting an enriching list of Tajweed skills, to develop them among student teachers, and to integrate technology in teaching those skills to help master them.